FENOMENA PENCURIAN KELAPA OLEH ANAK (Studi Kasus di Polsek Tembilahan Hulu) - Hilda Mianita; Kasmanto Rinaldi (UIR PRESS, 2020)
Juvenile delinquency is a common problem in society. There are norms or rules that lived in society. And it must be obeyed by society. Violation of norms and rules in society is not only committed by adults but also by juvenile. The violations of norms or rules that is often occurs by juvenile is theft. The theft that often occurs in Tembilahan is theft of coconuts, and it causes unrest in community. The majority of people in Tembilahan work as coconut farmers when the price of coconuts increases, coconut theft often occurs, not infrequently the perpetrators of coconut theft are the underage child or juveline. The purpose of this research is to determine what is the factors that cause the theft of coconuts by juvenile. This research uses a qualitative method by conducting interviews with key informants and informants that related to the topic. Referring to the theory used in this research, namely social control theory, this theory can explain why the phenomenon of coconut theft by juvenile occurs. The result of this research is that the theft of coconuts by juvenile occurs due to economic factors, in order to earn money the child or juvenile steals coconuts, it can also be explained through social control theory, which according to this theory, the child commits crimes or deviations due to the absence of attachment elements, commitment, involvement, and belief in theirself.